Study of the DTC P0108 Fault on a Suzuki XL7 Engine - Muhammad Andre (Politeknik Piksi Ganesha Indonesia, 2026)
This study aims to describe the analysis of the causes of problems in the engine of Suzuki XL7 with Diagnostic Trouble Code P0108. The analysis was conducted to identify the causes of this problem in the engine. The research method employed was a quantitative descriptive approach, utilising testing with a Scantool, Multy Tester and Vacuum Gauge. The testing procedure included engine preparation, instrument calibration, and the execution of diagnostics in accordance with established standard procedures. The research results indicate that the cause of the problem lies in the internal circuit of the MAP (manifold absolute pressure) sensor, with an O.L. (open-loop) measurement result, indicating no connection. This result was obtained by analysing the connections within the entire internal circuit of the MAP sensor. Overall, this study provides empirical information regarding the functioning of the MAP sensor in relation to the engine performance of the Suzuki XL7 following measurement analysis conducted in accordance with applicable procedures.